1989
DOI: 10.1029/jb094ib12p17907
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray production rates of 10Be and 26Al in quartz from glacially polished rocks

Abstract: We have studied the concentrations of 10Be and 26Al in quartz crystals extracted from glacially polished granitic surfaces from the Sierra Nevada range. These surfaces were identified with the glacial advance during the Tioga period ∼11,000 years ago. Our measurements yield the most accurate estimates to date for the absolute production rates of these nuclides in SiO2 due to cosmic ray nucleons and muons for geomagnetic latitudes 43.8°–44.6°N and altitudes 2.1–3.6 km. The estimates are relatively free from unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
435
3
10

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(456 citation statements)
references
References 27 publications
8
435
3
10
Order By: Relevance
“…Bromley et al [37] defined a lower moraine group (~5000-4900 m), extending to the lower area of the glacial valleys, as CI and a higher moraine group (~5500 m), deposited in the middle part of the Santiago valley, as CII. For each group of moraines they found two age ranges, depending on the scaling model used: Lm [70] or Li [71][72][73]: -CI moraines:~25-15 ka (Lm) and~21-12 ka (Li), with outlier ages~47 and~31 ka (Li) and~61 and~37 ka (Lm). -CII moraines:~11-12 ka (Lm) and~11-8 ka (Li).…”
Section: Snowlines Elas and Glacial Datingmentioning
confidence: 99%
“…Bromley et al [37] defined a lower moraine group (~5000-4900 m), extending to the lower area of the glacial valleys, as CI and a higher moraine group (~5500 m), deposited in the middle part of the Santiago valley, as CII. For each group of moraines they found two age ranges, depending on the scaling model used: Lm [70] or Li [71][72][73]: -CI moraines:~25-15 ka (Lm) and~21-12 ka (Li), with outlier ages~47 and~31 ka (Li) and~61 and~37 ka (Lm). -CII moraines:~11-12 ka (Lm) and~11-8 ka (Li).…”
Section: Snowlines Elas and Glacial Datingmentioning
confidence: 99%
“…The cosmogenic isotope technique is based upon the fact that cosmogenic nuclides accumulate in situ from exposure of, for example, quartz grains to cosmic rays at or near the land surface (e.g. Nishiizumi et al 1986Nishiizumi et al , 1989. Therefore it is possible to date the time at which an alluvial fan containing the measured sample was abandoned and left exposed, and, in principal, if a fan offset is measurable in that fan as it crosses the fault, then a slip rate can be determined.…”
Section: Quaternary and Holocene Offsetsmentioning
confidence: 99%
“…Zero-erosion model ages were calculated using a sea level high-latitude (SLHL) 10 Be production rate of 5.06 atoms/g quartz/yr. This production rate is based on measurements of glacial surfaces in the Sierra Nevada by Nishiizumi et al [1989] recalculated using the revised 13,000 years glacial retreat ages reported by Clark et al [1995], and rescaled for latitude and altitude using the coefficients of Lal [1991], as described by Owen et al [2002]. An uncertainty of 6% on the production rates [Stone, 2000] is considered.…”
Section: Appendix B: Sampling and Cosmogenic Datingmentioning
confidence: 99%